Effect of ethanolic extract of Centella asiatica on pentylene tetrazol induced seizure in albino mice - Kannoor, Ahmed A.; T., Ramani P. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Various preparations of the plant Centella asiatica were used in traditional medicine for treating memory disorders, insanity, epilepsy, headache, fever and dysentery. Hence this study was conducted to test the effect of Centella asiatica on classical animal model of epilepsy. Methods: First the ethanolic extract of Centella asiatica was subjected to acute toxicity study. Intraperitoneal injection of pentylene tetrazol in albino mice produces seizure. Plant extract was evaluated for protection from these experimental seizures. Four groups of animals were given the extract orally at 100mg, 200mg, 500mg and 1000mg per kilogram body weight. One group received phenobarbitone as standard drug and another group received distilled water as control. Time of onset of clonus is the study parameter. Statistical analysis of data was done using analysis of variance followed by Dunnet’s test. Results: Various doses of plant extract ranging from 100mg to 1000mg/kg exhibited protection from experimentally induced seizures. Compared to control, the plant extract showed statistically significant delay in time of onset of clonus. Conclusions: Centella asiatica is potential source of anti-epileptic drug. Detailed phytochemical studies and animal experiments are recommended.